Roles of Epithelial and Mesenchymal TRP Channels in Mediating Inflammatory Fibrosis - Okada, Yuka; Sumioka, Takayoshi; Reinach, Peter S.; Miyajima, Masayasu; Saika, Shizuya (Frontiers in Immunology, 2022)
The maintenance of normal vision is dependent on preserving corneal transparency. For this to occur, this tissue must remain avascular and its stromal architecture needs to be retained. Epithelial transparency is maintained provided the uppermost stratified layers of this tissue are composed of terminally differentiated non-keratinizing cells. In addition, it is essential that the underlying stromal connective tissue remains avascular and scar-free. Keratocytes are the source of fibroblasts that are interspersed within the collagenous framework and the extracellular matrix. In addition, there are sensory nerve fibers whose lineage is possibly either neural crest or mesenchymal. Corneal wound healing studies have been undertaken to delineate the underlying pathogenic responses that result in the development of opacification following chemical injury. An alkali burn is one type of injury that can result in severe and long- lasting losses in ocular transparency. During the subsequent wound healing process, numerous different proinflammatory cytokines and proteolytic enzymes undergo upregulation. Such increases in their expression levels induce maladaptive expression of sustained stromal inflammatory fibrosis, neovascularization, and losses in the smooth optical properties of the corneal outer surface. It is becoming apparent that different transient receptor potential channel (TRP) isoforms are important players in mediating these different events underlying the wound healing process since injury upregulates both their expression levels and functional involvement. In this review, we focus on the involvement of TRPV1, TRPA1 and TRPV4 in mediating some of the responses that underlie the control of anterior ocular tissue homeostasis under normal and pathological conditions. They are expressed on both different cell types throughout this tissue and also on corneal sensory nerve endings. Their roles have been extensively studied as sensors and transducers of environmental stimuli resulting from exposure to intrinsic modulators and extrinsic ligands. These triggers include alteration of the ambient temperature and mechanical stress, etc., that can induce pathophysiological responses underlying losses in tissue transparency activated by wound healing in mice losses in tissue transparency. In this article, experimental findings are reviewed about the role of injury-induced TRP channel activation in mediating inflammatory fibrotic responses during wound healing in mice.